Behavior of Muscle-Derived Stem Cells on Silica Nanostructured Substrates - Hyo-Sop Kim; Bit Na Lee; Sangdun Choi; Moon Suk Kim; Jae-Ho Kim (Nanomaterials, 2020)
The aim of the present work was to evaluate the responses of rat muscle-derived stem cells (rMDSCs) to growth on silica nanostructured substrates (SN) with nanoscale topographic surfaces. SN of different sizes (SN-60, SN-150, SN-300, SN-500, and SN-700) were prepared using silica nanoparticles with sizes of 60–700 nm. The prepared SN showed roughness at the nanoscale level. The total number of adherent cells on SN increased with increasing nanoscale level and incubation time. The rMDSCs attached to SN-500 and SN-700 were extensively flattened, whereas those grown on SN-60, SN-150, and SN-300 were more rounded. The rank order of the cell length and height of attached rMDSCs at 5 d on different surfaces was SN-60 ≈ SN-150 >> SN-300 > SN-500 > SN-700 > glass. Compared with rMDSCs grown on SN-60, SN-150, or SN-300, those attached to SN-500 and SN-700 exhibited a distinct morphology with filopodial extensions and stronger expression of focal adhesion, integrin, and actin. An evaluation of the gene expression of adhered rMDSCs showed that rMDSCs grown on SN-300 exhibited a higher environmental stress response than those grown on glass or SN-700. Collectively, our data provide fundamental insight into the cellular response and gene expression of rMDSCs grown on nanostructured substrates.